Colored Noises-Induced Regime Shifts in a Vegetation Ecological System*Supported by the National Natural Science Foundation of China under Grant No. 11305079, and the Introduction of Talent Capital Group Fund Project of Kunming University of Science and Technology under Grant No. KKZ3201407030. (1st August 2015) - Han, Qing-Lin; Zeng, Jia-Kui; Yang, Tao; Zhang, Chun; Long, Fei; Fu, Yun-Chang; Zeng, Chun-Hua
Abstract In this paper, we investigate the stationary probability distribution and mean first passage time in a vegetation ecological system, which is driven by cross-correlation between intrinsic and extrinsic colored noises as well as the nonzero cross-correlation in between. The impacts of the self-correlation time τ1 and τ2, the cross-correlation time τ3 and intensity k on the stationary probability distribution and mean first passage time are discussed, respectively. Our main results show that: (i) the self-correlation time τ1 can induce regime shifts from the desert state to the sustainable vegetation state, while the self-correlation time τ2, cross-correlation time τ3 and intensity k can induce regime shifts from the sustainable vegetation state to the desert state; and (ii) the self-correlation time τ1 or τ2 can enhance the stability of the sustainable vegetation biomass, while the cross-correlation time τ3 or strength k weakens the stability of the sustainable vegetation biomass.